2015
DOI: 10.1007/s00382-015-2647-5
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of statistical and dynamical downscaling models under the EURO- and MED-CORDEX initiative framework: present climate evaluations

Abstract: International audienceGiven the coarse spatial resolution of General Circulation Models, finer scale projections of variables affected by local-scale processes such as precipitation are often needed to drive impacts models, for example in hydrology or ecology among other fields. This need for high-resolution data leads to apply projection techniques called downscaling. Downscaling can be performed according to two approaches: dynamical and statistical models. The latter approach is constituted by various stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 128 publications
(129 reference statements)
1
71
0
1
Order By: Relevance
“…Several studies have compared different statistical and dynamical downscaling approaches and have illustrated that appropriate selection of approach needs to consider the advantages and limitations of each technique, availability of data and computational resources, and the kind of impacts being considered (e.g. Murphy, 1999;Gutmann et al, 2012;Hamlet et al, 2013;Giorgi and Gutowski, 2015;Ayar et al, 2016;Tang et al, 2016). In our case, to support multi-scale analysis of temperature (T) and precipitation (P) across the region, we have chosen to downscale the GCM projections to 1/16 ∘ resolution (∼5 ×7 km at mid-latitudes) at daily timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared different statistical and dynamical downscaling approaches and have illustrated that appropriate selection of approach needs to consider the advantages and limitations of each technique, availability of data and computational resources, and the kind of impacts being considered (e.g. Murphy, 1999;Gutmann et al, 2012;Hamlet et al, 2013;Giorgi and Gutowski, 2015;Ayar et al, 2016;Tang et al, 2016). In our case, to support multi-scale analysis of temperature (T) and precipitation (P) across the region, we have chosen to downscale the GCM projections to 1/16 ∘ resolution (∼5 ×7 km at mid-latitudes) at daily timescales.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of many of these methods has not yet been tested in urban areas, and work published in the literature to date provides very little information on their effectiveness at a smaller scale (1-10 km 2 ), such as in urban watersheds (Arnbjerg-Nielsen et al 2013;Willems et al 2012). Since downscaling is not an end in itself, but a process that provides necessary data and information to end-users (e.g., Vaittinada Ayar et al 2015), such global approaches are not very useful for estimating the impacts of CC on hydrologic budgets at a local scale.…”
Section: Statistical Downscalingmentioning
confidence: 98%
“…It is correct that analogsbased methods (e.g., Zorita and von Storch 1999) are unable by construction to generate values out of the range of the calibration dataset. However, stochastic downscaling models-or more generally, any model whose parameters or projections can evolve with the predictors-are able to generate downscaled values that have never been observed (e.g., Vaittinada Ayar et al 2015). For example, a recent study using linear statistical downscaling method (from the tool developed by Hessami et al 2008), realized on both temperature and precipitation variables, has demonstrated the capacity to generate plausible future changes in the severity and occurrence of droughts (an increase over the twenty-first century never observed over the historical period) in the Canadian Prairies.…”
Section: Statistical Downscalingmentioning
confidence: 99%
See 1 more Smart Citation
“…SDMs are based on a static relationship; i.e., the mathematical formulation of the relation between predictands (i.e., the localscale variable to be simulated) and predictors (i.e., the largescale information or data used as inputs in the SDMs) has to be valid not only for the current climate on which the relationship is calibrated, but also for future climates, for example. Most state-of-the-art SDMs belong to one of the four following families (Vaittinada Ayar et al, 2015): transfer functions, weather typing, methods based on stochastic weather generators and model output statistics (MOS) models, which generally work on cumulative distribution functions (CDFs). Many studies demonstrated that caution is required when interpreting the results of climate change impact studies based on only one downscaling model (e.g., Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%